-6y+2=-4(2y+4)

Simple and best practice solution for -6y+2=-4(2y+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6y+2=-4(2y+4) equation:


Simplifying
-6y + 2 = -4(2y + 4)

Reorder the terms:
2 + -6y = -4(2y + 4)

Reorder the terms:
2 + -6y = -4(4 + 2y)
2 + -6y = (4 * -4 + 2y * -4)
2 + -6y = (-16 + -8y)

Solving
2 + -6y = -16 + -8y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '8y' to each side of the equation.
2 + -6y + 8y = -16 + -8y + 8y

Combine like terms: -6y + 8y = 2y
2 + 2y = -16 + -8y + 8y

Combine like terms: -8y + 8y = 0
2 + 2y = -16 + 0
2 + 2y = -16

Add '-2' to each side of the equation.
2 + -2 + 2y = -16 + -2

Combine like terms: 2 + -2 = 0
0 + 2y = -16 + -2
2y = -16 + -2

Combine like terms: -16 + -2 = -18
2y = -18

Divide each side by '2'.
y = -9

Simplifying
y = -9

See similar equations:

| 6.5y=-63.7 | | -3+x-5=-13+9-8 | | 20X+10Y=-10X+15X-5Y | | 2x-5*2=25 | | 0=x^2+2x+6 | | x^5=0.4 | | 3x+40=50+2x | | 8-7x=37-14x | | 4x+6=-106-10x | | 26X^2-9X=0 | | x^4-13x^2+36= | | 5x+13=2x-23 | | 2x-7=33 | | -3(t-8)-(t+3)=1 | | n=0.04x-78.70 | | -17=x+23 | | 8a-6=6y+2 | | 28x^2+19x-5=-8 | | 0.33(10x+27)=-0.2(18.33x+25) | | 0.7(3x-20)=22-3.9x | | 180-2x=34x+24 | | 11n-9=6n+29 | | 26x^2-9=0 | | 1.6(1.5x+7.5)=0.6(6x+30) | | y=.75x-2 | | (-2(14x-2))=((9x+8)(x-3)) | | -22-10x=10x-18 | | 28t^2-46+16=0 | | 9x^2-7x-28=0 | | -3x-8=10 | | .4(3x+8)=.2(x+5) | | 123-4x=5x+15 |

Equations solver categories